Cidade e fotografia: espaços e histórias na produção do fotógrafo Ângelo Naguettini: Uberlândia (1940-1950) - Simão, Pâmela Aparecida Vieira (2015)
The purpose of this research is to investigate the city of Uberlândia from Angelo Naguettini s photo production, seeking to understand the meanings made in the narrative of his photos produced in the 40 s and 50 s on the city, in the relationships that people establish there. Angelo Naguettini s images gained significant evidence through their uses and appropriations in various circuits and are still present in different spaces at the time of this research, reproduced in newspapers, magazines and academic works, also in public spaces, postcards and other media, providing senses of the city. The analysis of these images reproduced in several places and material media allowed to verify a common repertoire in its production, relative to the focus, framing and photographed places, among other variables, showing a constancy in the way it gives visibility to the city, privileging an urban area with a recurring register of certain avenues, squares and buildings, present in various circuits and also in the photographer\'s collection. Grasp the movement of Angelo Naguettini s photography in its various uses and /or appropriations in/by the city instigate us to investigate the historicity of his photos, based on the assumption that the photographic language is constitutive of the social